PREVALENCE OF MALNUTRITION AMONG SCHOOL AGE CHILDREN INSABON GARI LOCAL GOVERNMENT AREA, KADUNA STATE - Olagunju, Abbas; Halimatu, Sadiya Abdullahi; Olumuyiwa, Adeyemi Owolabi (FUDMA JOURNAL OF SCIENCES, 2025)
The study assessed the prevalence of malnutrition among school-age children in Sabon Gari Local Government Area, Kaduna state, using a multi-stage cross-sectional study design. Two hundred and ninety-seven school-age children of both sexes were selected and standard anthropometric techniques were used as described by WHO. Socio-demographic analysis revealed that 86.2% of the children attend  schools. Gender balance was observed, with 49.8% males and 50.2% females. The majority of the school- age children belong to the Hausa ethnic group (73.8%), followed by Fulani (12.4%), Yoruba (4.8%), and Igbo (4.8%) ethnic groups. Fathers of school-age children were primarily civil servants (42.5%), while their mothers were predominantly involvedtrading (46.6%). Anthropometric indicators of Weight-for-Age Z score (WAZ) indicated that 37.1% of the children had normal weight-for-age, 25.2% were moderately underweight (< -2 Z score) and 1.4% were severely underweight (
Keywords: Undernutrition; anthropometry; stunting, underweight wasting; public health; school-age children; Sabon Gari; Nigeria